PENINGKATAN KAPASITAS DAN AKUNTABILITAS KINERJA BIROKRASI DAN INDIKATOR SERTA MODEL PENGUKURANNYA - Kartiwa, H.A (Jurnal Desentralisasi, 2012)
Accountability is an obligation embodiment of a government institutions to take responsibility for the success and failure of its mission. Implementation of accountability through a strategic approach, which will accommodate the rapid changes occurring in the organization and quickly adapt to changes as the demands anticipatory stakeholders concerned. Implementation of accountability and external examination itself is needed as one of the pillars for the creation of good governance and clean government. Democratic climate in public bureaucracies inspire trust and mutual trust between the government and the public. A clear division of powers and balance between the state create an conducive atmosphere to the built of the nation and the state.